In silico molecular docking approach and in vitro cytotoxic, antioxidant, antimicrobial and anti-inflammatory activity of Ixora brachiata Roxb. (January 2023) - Veeramuthu, Kamaraj; Annadurai, Pushparaj; Gideon, Daniel A.; Sivaramakrishnan, Ramachandran; Sundarrajan, Balamurugan; Dhandayuthapani, Kandavel; Pugazhendhi, Arivalagan
Abstract: The Ixora brachiata Roxb. methanolic leaf extract yielded significant in vitro free radical scavenging activity against DPPH (60% of inhibition obtained in 100 μg/mL) and ABTS (62% of inhibition obtained in 100 μg/mL) radicals, compared to ascorbic acid positive control. The antibacterial activity was modest when compared with antibiotics controls. The extract was effective, especially against Escherichia coli and Staphylococcus aureus, yielding 5 ± 0.9 (mm) and 4 ± 0.5 (mm), respectively, at a 10 mg/mL concentration. MTT assay showed an IC50 value of 51 μg/mL. The plant extract was rich in antioxidants, and anthraquinones were detected. When compared to aspirin (100–800 μg/mL) which had much greater anti-inflammatory (HRBC stabilisation) activity of 45–84%, the methanolic extract of I. brachiata was found to possess 10–45% activity in the same concentration range of 100–800 μg/mL. Since aspirin is a pure compound (and a routinely employed anti-inflammatory standard) and the plant extract contains multiple compounds with differential anti-inflammatory activities, the activity of aspirin may have been much higher. Qualitative and quantitative analyses showed the presence of different classes of primary and secondary metabolites in the leaf extract. The GC-MS (Gas chromatography-mass spectrometry) study in the plant extract showed that ∼22 different volatile compounds were present. The in vitro cytotoxic potential of the extract was assessed in MCF-7 breast cancer cell lines, and the bioactive compounds β-sitosterol, γ-sitosterol, δ-tocopherol and squalene, which were identified through GC-MS, were further assessed for binding to salient receptor proteins which are routinely involved in breast cancer pathophysiology, like PI3K, MMP-9, mTOR and ERβ. Graphical Abstract: ga1 Highlights: Ixora brachiata Roxb . from Rubiaceae has potent medicinal properties. The methanolic leaf extract inhibited MCF-7 cells with IC50 of 51 μg/mL. The extract was rich in antioxidants and over 20 metabolites were detected in GCMS. Metabolites' interactions were explored against breast cancer targets via docking.